Looking Back and Moving Forward: A Meta-Analytic Review and Two Original Studies Examining the Role of Action Planning and Coping Planning in Promoting Physical Activity Behaviour - Carraro, Natasha Olga Norina (Université d'Ottawa / University of Ottawa, 2015)
Physical activity (PA) offers numerous physical and mental health benefits. Unfortunately, most people struggle to lead an active lifestyle, particularly when they are concurrently striving to balance other pursuits that may interfere with their engagement in PA. The self-regulatory strategies of action planning (AP) and coping planning (CP) have been proposed as a means of helping people initiate and maintain PA, though inconsistent findings have been observed to this effect. The primary objectives of the present dissertation, achieved by way of two original articles, were to (a) review the extant planning for PA literature in order to summarize and synthesize knowledge in the area to date, and (b) examine AP and CP in relation to more than one goal at a time, while testing the relevant moderator of academic goal conflict. The first article comprised a meta-analysis of correlational (k = 19) and experimental (k = 21) studies on planning for PA, which revealed a medium-to-large summary effect for correlational studies, and a small summary effect for experimental studies. Furthermore, AP and CP emerged as partial mediators in the relation between behavioural intention and PA. Numerous moderators were also found. Among other key findings, this article cast light on the fact that, despite multiple goal pursuit being the rule rather than the exception, most studies reviewed examined a single goal in isolation. Further, the summary effects found were more modest than expected and highly heterogeneous, pointing to the value to testing relevant moderators. Thus, the second article contained two studies that examined the moderating role of academic goal conflict on the relations between AP and CP with PA using samples of university students concurrently pursuing an academic and a PA goal. Study 1 (N = 317) used a 6-week prospective design, and Study 2 (N = 97) used a 1-week daily diary design and measures of self-reported PA behaviour and goal progress. Across both studies, it was found that academic goal conflict moderated the influence of planning on PA outcomes. AP and CP were found to play differential roles in predicting PA when students were experiencing goal conflict: AP related to better PA outcomes at lower levels of academic goal conflict, whereas CP related to better PA outcomes at higher levels of academic goal conflict. These two self-regulatory strategies appear to play a different, yet complementary role in the goal pursuit process. Overall, the present dissertation contributes to knowledge synthesis in the area of planning for PA. In addition, novel research findings are presented which specifically target identified gaps in the literature. Theoretical, methodological, and practical implications are discussed, and future research avenues are proposed.
Keywords: Self-regulation; Physical activity; Goal striving; Multiple goal pursuit; Action planning; Coping planning; Meta-analysis; Intraindividual